Survival Analysis of Risk Factors for Mortality in a Cohort of Patients with Tuberculosis - Yi Xie; Jing Han; Weili Yu; Junping Wu; Xue Li; Huaiyong Chen (Canadian Respiratory Journal)
Identify the treatment effects and risk factors for mortality in patients with pulmonary tuberculosis receiving antituberculosis treatment under the Directly Observed Treatment Short-Course (DOTS) program to reduce the mortality rate of tuberculosis. A retrospective cohort analysis was conducted on the outcomes of antituberculosis treatment of 7,032 patients with tuberculosis in the DOTS program, in the Tuberculosis Management Information System from 2014 to 2017 in Tianjin, China. The Kaplan–Meier method and multifactor Cox proportional risk regression model were used to analyze the risk factors for mortality during antituberculosis treatment under DOTS. The success rate of antituberculosis treatment was 90.24% and the mortality rate was 4.56% among 7,032 cases of tuberculosis in Tianjin. Cox regression analysis showed that advanced age, male sex, human immunodeficiency virus (HIV) positivity, first sputum positivity, retreated tuberculosis, and a delayed visit (≥14 days) were risk factors for mortality in patients with pulmonary tuberculosis receiving antituberculosis treatment under DOTS. The treatment effects in patients with pulmonary tuberculosis during antituberculosis treatment under DOTS were positive in Tianjin. Advanced age, male sex, HIV positivity, first sputum positivity, retreated tuberculosis, and a delayed visit (≥14 days) increased the risk for mortality during antituberculosis treatment.